The evolution of woman issues description in Kazakh periodicals - Seidigazimova Ш.Д.; Tapanova С.Е.; Тoplu М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The media is not only a link between the government and the people, but also the fourth estate. Today many media outlets are constantly working in the field of information exchange. Among them, our national press, which has become the spiritual food for the cultural life of the reader, exerts a tremendous influence on the customs and traditions of society, regardless of what it is about. The Kazakh press plays a special role in achieving gender equality as the most sensitive indicator of the state of society, and it is clear that the research article is based on a topical and important topic of our time. Main results. The article examines the history of the formation of the first women’s publications in the early twentieth century, which takes into account the published works of art by women writers and their topics as a scientific basis. The frequency and specificity of the presentation and writing of the problem of gender equality in publications are determined, and the analysis of materials substantiates paradoxical tendencies. The relevance of research. There has been carried out a comparative analysis of articles on women’s issues in the Kazakh press based on historical data; a special place in the press is given to the presentation of the first women’s publication and honored women writers as an example for today’s generation.